STUDI LONGITUDINAL TERHADAP KUALITAS UDARA DAN KEJADIAN PENYAKIT PARU DI KOTA MEDAN: ANALISIS PENGARUH JANGKA PANJANG - MAESSTRO BINA UTAMA SIMANJUNTAK (JURNAL ILMIAH KOHESI, 2023)
Medan City is one of the cities that should have a bad level of air pollution, where in the last year the air quality in Medan City reached PM 15, where this kind of quality indicates that the air quality in Medan City is not good. This will affect the quality of human life, where the quality of human life is related to lung health which is a place for human breathing, so that with poor air quality in Medan City will have an impact on lung damage through penunomia disease (shortness of breath), where there are around 2430 residents affected by this disease. The population of this study amounted to 2430 people in Medan City who were affected by lung disease and hospitalized, where the samples taken amounted to 64 respondents who were people in Medan City who were affected by lung disease and hospitalized. Data collection techniques are carried out by observation and documentation studies. The results of the study proved that Medan Kota District is the area in Medan City that tends to state the most bad air quality, and is affected by many lung diseases, where the residents affected by this disease are female residents, self-employed professions and affected by this disease in the age range of 30-39 years